Perancangan Sistem Informasi Bank Sampah Kota Bandung Berbasis Website - Ira Ayu Wulandari; Mohamad Satori; Ahmad Arif Nurrahman (Bandung Conference Series: Industrial Engineering Science, 2022)
Abstract. Waste Bank is a system related to collecting recyclable waste which, is then deposited into the recycling mechanism. The service process in the Waste Bank is currently still manual. Namely, by recording in the passbook, there is no integrated system between the household, the Waste Bank unit, the central Waste Bank, and the industry that will recycle materials into specific products. Results in inefficiency in the management of the Waste Bank. For this reason, this article raises the issue of how to develop an information system for the Bandung City Garbage Bank based on the case study website of the Garbage Bank in the City of Bandung. The information system that the author developed in this study uses the Rapid Application Development (RAD) method, which has three stages (1) The requirements planning stage identifies the purpose of the system. (2) The workshop design stage models the results of logical and physical analysis and definition, including functional and non-functional requirements, modeling activities or system interactions using Use Case Diagrams, process modeling using Business Process Modeling, and Notation 2.0 (BPMN 2.0), and data modeling using Entity-Relationship Diagrams. (3) The implementation phase carries out the realization of the user’s system design made and agreed upon by the user covering various aspects such as database development using PHP MySQL and the interface using PHP-based CodeIgniter. The results of this study are: the designed system can access by customers, BSU, BSI, and industry according to the needs of each user, all data is stored in a database on one server so that can access it online. Abstrak. Bank Sampah adalah suatu sistem yang berkaitan dengan proses mengumpulkan sampah layak daur ulang yang kemudian disetorkan ke mekanisme daur ulang. Proses pelayanan di dalam Bank Sampah saat ini masih manual yaitu dengan melakukan pencatatan di buku tabungan, tidak adanya sistem yang terintegrasi antara pihak rumah tangga, Bank Sampah unit, Bank Sampah induk dan industri yang akan mendaur ulang material menjadi produk tertentu. Hal ini berakibat pada ketidakefisienan dalam tata kelola Bank Sampah. Untuk itu maka artikel ini mengangkat permasalahan bagaimana mengembangkan sistem informasi Bank Sampah Kota Bandung berbasis website studi kasus Bank Sampah di Kota Bandung. Sistem informasi yang penulis kembangkan dalam studi ini menggunakan metode Rapid Application Developmen (RAD) yang memiliki tiga tahapan yaitu (1) Tahap requirement planning melakukan identifikasi terhadap tujuan sistem. (2) Tahap workshop design memodelkan hasil analisis dan pendefinisian secara logis dan fisik meliputi kebutuhan secara fungsional dan nonfungsional, pemodelan aktivitas atau interaksi sistem menggunakan Use Case Diagram, pemodelan proses menggunakan Bussiness Process Modeling and Notation 2.0 (BPMN 2.0), dan pemodelan data menggunakan Entity Relationship Diagram. (3) Tahap implementation melakukan perwujudan dari rancangan sistem yang telah dibuat dan disepakati oleh pengguna meliputi berbagai aspek sepeti pembangunan basis data menggunakan phpMySQL dan antarmuka menggunakan CodeIgniter berbasis PHP. Hasil dari penelitian ini adalah: sistem yang dirancang dapat diakses oleh nasabah, BSU, BSI dan industri sesuai dengan kebutuhan dari setiap pengguna, seluruh data tersimpan pada databse dalam satu server sehingga dapat diakses secara online.